Analysis of perspectives and public policies focused on electric public transportation - bus mode in Costa Rica (2018-2022) - Díaz-Arrieta, José Pablo (2025)
This work provides a general analysis of public policies focused on electric bus transportation in Costa Rica during the years 2018-2022. To achieve this, it includes a documentary analysis of Costa Rica’s legal framework that promotes electric mobility, decarbonization plans, and the reduction of Greenhouse Gas Emissions (GHG), as well as the laws that establish institutional competencies for the implementation of electric buses. Additionally, it incorporates an analysis of semi-structured interviews with stakeholders from the Legislative Assembly, the Costa Rican Electricity Institute (ICE), the German Cooperation Agency (GIZ), and the Directorate of the National Public Transportation Council (CTP). Based on the analysis, it is concluded that there are significant institutional barriers and economic limitations that hinder the implementation of electric buses, but there is evidence of opportunities to develop negotiation models with the bus sector in order to improve the public transportation system for the benefit of the public interest.